What Hitchcock Taught Us about Whodunnits - Dominique Sipière (Sillages Critiques)
Although he specialised in crime thrillers, Alfred Hitchcock avoided filming whodunnits: his dislike gives a clue to both readers and spectators about the nature of what could be termed a “Hitchcock-genre” and about the thrill some still get from seemingly old fashioned novels of the 1930s. Whodunnits follow a strict pattern of double narration (the inquest strives to recreate the hidden story of the crime) and of a double “game” (the “author” challenges the reader and the characters keep challenging each other). But the main thrill might result from a specific tension between a logical quest and an ever expected meta-religious instant of revelation: doubt and certainty, mastery and subversion.